Viktorijanska biopolitika, psihoanaliza i Sherlock Holmes: "Skrletna studija" - Jukić, Tatjana (Array, 2014)
Taking up Arthur Conan Doyle’s A Study in Scarlet (1887), the first Sherlock Holmes narrative, I argue that the raison of the Victorian detective story depends on situating the subjectivity as it forms and explains itself in the Victorian Bildungsroman, against the logic of Victorian political economy. This happens not least where the Holmes narratives show that subjectivity sustains itself only insofar as it manages to subject law to various micronarratives of capitalization. While this is how the Holmes narratives anticipate what at that point was yet to form as psychoanalysis, they also adumbrate its (Deleuzian) critique ; further, this is where a peculiar Victorian biopolitics can be discerned. Finally, I propose that America of A Study of Scarlet is critical to the above configuration, with the American Revolution as the event constituent of Victorian culture.